Hubungan Riwayat Kejang Demam dengan Kejadian Epilepsi pada Anak di Rumah Sakit Santa Elisabeth Lubuk Baja Kota Batam - Suryanti Suryanti; Efilona Setri; Fadhil Ahmad (Universitas Batam, 2022)
Background: Epilepsy is a disease that can reduce the quality of human life characterized by epileptic seizures. Many epilepsy cases in Indonesia are still undetected, many people with epilepsy do not visit health centers because they do not know about the disease. The exact cause of epilepsy is not known. Children who have a history of febrile seizures can cause epilepsy. Methods:The method of this research is descriptive analytic with cross sectional approach which is conducted at Santa Elisabeth Lubuk Baja Hospital, Batam City. The sample in this research uses the formula of Slovin and obtained a total sample of 98 people. Data were collected using medical records. The data obtained werw analyzed using the Chi-Square test. Results:The results of the analysis of pediatric epilepsy based on abnormal EEG patients had a history of febrile seizures as many as 25 children (37.9%) while those without a history of febrile seizures were 41 children (62.1%). Children with epilepsy based on clinical had a history of febrile seizures as many as 5 children (15.6%) while those without a history of febrile seizures were 27 children (84.4%). The results obtained p value of 0.045, meaning that there is a significant relationship between a history of febrile seizures and the incidence of epilepsy. Conclusion:There is a correlation between a history of febrile seizures and the incidence of epilepsy in children at the Santa Elisabeth Lubuk Baja Hospital, Batam City in 2021.